ABC‐Type meso‐Triaryl‐Substituted Subporphyrins (Eur. J. Org. Chem. 19/2014). Issue 19 (July 2014) - Yoshida, Kota; Mori, Hirotaka; Tanaka, Takayuki; Mori, Tadashi; Osuka, Atsuhiro
Abstract : The cover picture shows Takamatsu‐zuka Tomb, a dome‐shaped ancient burial mound located in Asuka Village, Nara Prefecture, Japan. The dome‐shaped Takamatsu‐zuka Tomb is reminiscent of the domical geometry of a subporphyrin. ABC‐type subporphyrins bearing three different meso substituents were synthesized by a condensation reaction of AB‐type tripyrrane with aroyl chloride using boron as a template. Various aryl groups can be introduced at the meso positions, with some of them inducing dramatic changes on the optical properties. As a result of their domed structure, ABC‐type subporphyrins, in theory, should be chiral. Indeed, two enantiomers were observed in crystal motifs and successfully separated by chiral HPLC. Details are discussed in the article by T. Mori, A. Osuka et al. onp. 3997 ff.